Implementasi Konsep Keberlanjutan dalam Pelayanan Pelanggan Department Bar Melalui SOP Pengelolaan Sampah di Jambuluwuk Oceano Seminyak Hotel - Kadek Deva Wardana; Trianasari Trianasari; Nyoman Dini Andiani (Jurnal Manajemen Riset Inovasi, 2026)
This study aims to analyze the implementation of sustainability principles in customer service within the Bar Department through the application of the Standard Operating Procedure (SOP) for waste management, as well as to identify the challenges and strategies adopted by bar staff at Jambuluwuk Oceano Seminyak Hotel . Employing a descriptive qualitative approach, data were collected through semi-structured interviews, observations, and documentation involving informants from the HR Department, Bar Manager, and Bar Supervisor to obtain comprehensive insights from policy formulation to on-site operational practices. The findings indicate that sustainability efforts such as reducing single-use plastics, implementing a straw on request policy, and providing segregated waste bins have been introduced; however, these efforts are not fully integrated into formal SOPs, resulting in inconsistent implementation that largely depends on staff initiative, particularly during peak operational hours. Key challenges include limited supporting facilities, insufficient training on sustainability, and conflicts between rapid service demands and proper waste segregation. Nevertheless, bar staff have employed adaptive strategies such as end-of-shift waste sorting, reducing unnecessary plastic use, and maintaining internal communication to ensure compliance. This study highlights the need for a more comprehensive waste management SOP, continuous sustainability training, and improved facilities to strengthen consistent and systematic sustainability practices within bar service operations.